ANALYZING A SPEECH AND GRAMMAR USE FATHIA IZZATI AND NESSIE JEDGE IN THE VIDEO OF CARA BERBAHASA INGGRIS LANCAR - Muhamad Nana Nahroji; Acep Haryudin; Leni Andriani (IKIP Siliwangi, 2020)
AbstractIn this research used qualitative research method, qualitative research is “a situated activity that locates the observer in the world. It consist of set of interpretive, material practices that make the world visible. These practice transform the world and in this research would be find out how speech and grammar used by Fathia Izzati and Nessie Jedge in the video of Cara Berbahasa Inggris dengan Lancar. In this research, finding the conclusion from video cara berbahasa inggris by Nessie Jedge and Fathia, there are many word used in their conversation its like anaphoric, textual theme, reference, topical theme and comparative reference. And the second analyze finding some mistakes in their conversation still not using grammatical appropriate.Keywords: Discourse Analysis, Video, Grammar